Global, Local or Glocal?: The debate continues. Issue 45 (March 2014) - Mareck, Manfred
Abstract : In 1983, Theodore Levitt published "The Globalization of Markets" in the Harvard Business Review. His notion of the global village lead (at least in part) to the myth of global brands.